The effects of injury, contextual match factors and training load upon psychological wellbeing in English Premier League soccer players via season-long tracking - Grimson, S.; Brickley, G.; Smeeton, N. J.; Abbott, W.; Brett, A. (European Journal of Sport Science, 2022)
The study aimed to track psychological wellbeing (PWB) across two consecutive soccer seasons examining the effects of injury, illness, training load (TL) and contextual match factors (playing status, match selection and individual win rate). Furthermore, examine PWB prior to injury or illness event. Thirty-two English Premier League (EPL) soccer players completed the "Warwick-Edinburgh Mental Wellbeing Scale" every two weeks. No differences were found for group averaged PWB across the seasons (52.2 ± 0.3 vs. 51.8 ± 1.1) (p > 0.05). Previous 7-day TL measured using GPS (session duration, total distance, explosive distance, low-intensity distance, high-speed distance (HSD) and sprint distance (SD)) were not related to current PWB (p > 0.05). Yet, previous 14-day HSD (r (385) = -0.095) and 21-day SD (r (385) = 0.100) were related to current PWB (p < 0.05). Only 100% (vs. 0%) win rate in the previous 14-days to the questionnaire revealed a higher current PWB score (52.7 ± 4.7 vs. 50.9 ± 5.6 (p < 0.05)). PWB did not differ prior to an injury or illness event, when players were injured or had low contextual match factors at time of questionnaire or previous match, and the previous 7-days (p > 0.05). In conclusion, PWB fluctuations across the season are associated with prior TL and multiple negative results. But prior PWB was not linked to injury or illness events. Implications for prioritising interventions to improve PWB during periods of chronic high intensity TLs and losing streaks, monitoring PWB, and use in injury and illness prediction are discussed.